Immortalized cementoblasts and periodontal ligament cells in culture - D’Errico, J.A; Ouyang, H; Berry, J.E; MacNeil, R.L; Strayhorn, C; Imperiale, M.J; Harris, N.L; Goldberg, H; Somerman, M.J (Bone (New York, N.Y.), 1999)
Cementum, a mineralized tissue lining the surface of the tooth root, is required for formation of a functional periodontal ligament attachment during development. Additionally, during regeneration of tissues after disease, cementum is thought to play a critical role in the reparative process. Research efforts aimed toward understanding mechanisms involved in periodontal development and regeneration, and in particular the formation of root cementum, have been hampered by an inability to isolate and culture cells involved in cementum production, i.e., cementoblasts. Using classical techniques for osteoblast isolation, immortalized, heterogeneous cementoblast/periodontal ligament cell (CM/PDL) populations were established from cells lining the tooth root surface of: 1) CD-1 mice, where cells were immortalized using SV40, or 2) H-2K btsA58 “immorto” mice, where cells containing an immortalizing transgene were removed and cultured. CM/PDL populations were derived from tissues adherent to developing tooth root surfaces, while tissues adherent to the surrounding alveolar bone were specifically excluded from the population. Immortalized CM/PDL cells were characterized to ensure their phenotype reflected that previously demonstrated in situ and in primary, nonimmortalized cultures. Proteins/mRNAs associated with bone/cementum and known to be expressed by root lining cementoblasts, but not by PDL cells, in situ, e.g., bone sialoprotein, osteopontin, and osteocalcin, were expressed by cells within the immortalized populations. Furthermore, CM/PDL cells, in vitro, attached to bone sialoprotein in an arginine-glycine-aspartic acid (RGD)-dependent manner, promoted mineral nodule formation and exhibited a PTH/PTHrP-mediated cAMP response. These immortalized heterogeneous populations, containing both CM and PDL cells, provide a unique opportunity to study cells involved in cementogenesis and to enhance our knowledge of the mechanisms controlling development, maintenance, and regeneration of periodontal tissues.